Learning Strategies for Children with Learning Difficulties and Their Relationship to Emotional Intelligence in Light of the Challenges of Social Media: An Applied Study to Measure Social Adaptation - Alsubaie, Mohammed Munahi; Alsaadi, Faris Abdullah Hamed; Almulla, Mazen Omar; Almulla, Abdullah Ahmed (Journal of Posthumanism, 2025)
This study examines the relationship between learning strategies and emotional intelligence in children with learning disabilities, particularly in light of the challenges social media poses to their social adjustment. With the increasing influence of digital platforms on children's emotional and cognitive environments, children with learning disabilities face unique challenges in balancing academic, emotional, and social demands. The study aims to understand how effective learning strategies, when coordinated with emotional intelligence, contribute to improved social adjustment outcomes. An applied quantitative methodology was adopted, using standardized psychometric tools to assess learning strategies, emotional intelligence, and levels of social adjustment in a targeted sample of children diagnosed with learning disabilities in the Kingdom of Saudi Arabia. Data were collected through structured questionnaires completed by teachers and specialists in inclusive educational settings, with 55 teachers participating. Statistical analyses relied on methods such as correlation and regression to test the study's hypotheses and analyze the strength and direction of relationships between various variables. The results are expected to provide evidence on the role of emotional intelligence as a mediating factor in promoting adaptive learning behaviors, as well as on how digital challenges influence these dynamics. The study provides results of great importance to educators, psychologists, and decision-makers, as it contributes to the design of targeted interventions to enhance cognitive and emotional resilience among students with learning difficulties in the digital age, particularly within the Saudi education system.